Negatória de paternidade: uma análise sob a ótica do pai - Costa, Denise Cristina Garcia [UNESP] (2014)
This dissertation concerns the study of current issues denies paternity, which has been a recurring problem in the family courts and the Probate district of Uberlândia, as well as in other Brazilian courts, demands that have grown in the face of the emergence of DNA testing in 1985 and their socialization in the mid -2000s. axles drivers of research were the theoretical foundations and field research through the use of an interview with semi - structured instrument given to the parents that they entered with the action of denies paternity in the sticks Family and Succession in the region of Uberlândia - MG, Courthouse Abelard Penna and who were referred to the Social Services industry in the years 2010-2013. 's main objective was to identify affective paternity must be viewed with the same principles of biological paternity. For better understanding of the subject, the theoretical framework permeated the dawn of civilization to the present day, trying to understand the process of family building and corporate training, passing by many family models that have been built throughout history. The study universe was 6 individuals who perpetrated action denies paternity in the family courts of the District of Uberlândia - MG. We also performed by sampling the documentary research of 16 cases that were processed in their family courts and Probate and were directed to the Department of Social Services, processes that have been filed , which enabled us to visualize the process and the result , ie if the request was granted or denied denies by court Judge . Thus we conclude that the influences of society grounded in private property, in the female monogamy, influence men not to accept his son’s betrayal arising seeking subterfuge to evade the responsibility gained as to claim that there was no affection with the child even before the evidence of DNA testing